CAPACIDAD ECONÓMICA COMO MECANISMO DE SUMISIÓN DE LA VÍCTIMA DE VIOLENCIA E INSERCIÓN LABORAL EN LA LUCHA CONTRA LA VIOLENCIA FAMILIAR, PUNO - 2017 - MENDIZABAL LUQUE, MIRELLA PAOLA (2020)
The objective of this research is to carry out a study on the economic capacity as a mechanism of submission of the victim of violence and labor insertion in the fight against family violence. Violence is a phenomenon present in all societies, and has diverse consequences, as well as the labor and economic impact of violence against women. The economic dependence of women is an issue that makes the sea happen before man, which until now has no escape from the influence of the patriarchal structure that prevails in society and this puts women at a disadvantage labor and economic in front of man. Cases of conjugal violence are of great concern to physical and psychological abuse, due to factors that affect the mental health of members of the family, leaving physical and psychological consequences.